Politics, Centralisation and Service Delivery in Urban Zimbabwe. Issue 5 (3rd September 2018) - Muchadenyika, Davison; Williams, John J.
Abstract : The politics of urban control has revolved around centralisation since independence in 1980. However, such politics became more pronounced after 2000 owing to the rise of the opposition Movement for Democratic Change (MDC) as the main governing party in urban areas. Political tensions and contradictions ensued between central government, under the Zimbabwe African National Union (Patriotic Front) (ZANU[PF]), and local authorities, under the MDC, over the control and administration of urban areas. Based on 30 interviews, the article explains how central government and, by extension, ZANU(PF) attempted to regain control of urban areas through centralisation of water and vehicle licensing functions. This practice, however, contravenes existing laws. Hitherto, scholarship has attributed centralisation by the government to a strategy to defuse the opposition rule in cities. This article extends reasons for centralisation to include ZANU(PF)'s strong ideological belief in centralisation, access to resources in a failing economy and maintaining a firm grip on power. In particular, the article focuses on how urban politics is manifested in the transfer of water and sanitation and vehicle licensing functions from local authorities to government-run entities. It is also evident that the prioritisation of survival politics neglects key service delivery in urban centres. In the absence of a functionally devolved system of governance, this casts doubt on the feasibility and success of opposition political parties in governing African cities.